GAMBARAN PENGGUNAAN SUKRALFAT PADA PASIEN GASTRITIS RAWAT INAP PENYAKIT DALAM DI RS.HASANUDDIN DAMRAH BENGKULU - Dewi Winni Fauziah (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram)
Gastric is one of the important organs in the human body. Cases related to damage to gastric mucosal integrity, one of which is gastritis. Gastritis cases are still the biggest disease problem in Indonesia and based on datathat obtained from the Bengkulu City Health Office, gastritis is ranked third with the highest number of hospitalizations in hospitals. One of the drugs used in treatment options in cases of gastritis is sucralfate, both used alone and in combination with other drugs. The aim of this study was to see an overview of the use of sucralfate in gastritis cases at Hasanuddin Damrah Hospital Bengkulu. The design of this study was non-experimental where the method of data retrieval is retrospective by taking secondary data from medical records and processed descriptively with a sample of 92 people describing the characteristics of gastritic patients using sucralfate drugs based on sex, age, combination drug use, complaints that arising and other comorbidities presented in table form. The results showed that female patients (57%) had more cases of gastritis than men, with the most felt nausea complaints (42.93%), and were more prevalent in the adult age group (20-50 years) ie 52 , 1%. The most widely used combination drug used by patients was ranitidine injection (55.43%) and the most common comorbidities experienced were dyspepsia (36.95%).